Topical Nitroglycerine Versus Lateral Sphincterectomy for Fissure in Ano: A Hospital Based Comparative Study - Adhikari, Bimarsh; Yadav, Sunil Kumar; Gupta, S. N. (Journal of Nepalgunj Medical College, 2018)
Background: Anal fissure is a common benign condition presenting as severe pain, constipations and bleeding per rectum. It is defined as longitudinal tear or defect in anal canal skin. Surgical treatment of this conditions requires hospital admission and complications, like bleeding, infection and to its severe extent continence disturbances. That warrants a new treatment modality as pharmacological sphincterotomy i. e topical GTN (glycerine trinitrate) whose effects are reversible, cost effective and simple.Objective: The objective is to compare the effectiveness of topical GTN over lateral sphincterotomy in terms of pain management and healing of fissure.Method: This was a comparative study carried out in the department of Surgery at Nepalgunj Medical College, Teaching Hospital. Two groups were created and 25 patients in each group were put randomly. First group (Group 1) used topical GTN whereas second group(Group 2) underwent lateral sphincterotomy for treatment of fissure. The two groups were reassessed at 4 and 8 weeks for pain and fissure healing.Result: Total number of patients was 50. Each group consisted of 25 patients. The male to female ratio in group 1 was 1:1.5 and in group 2 it was 1: 1.8. In group 1 patients after 4 weeks of application of GTN pain reduced from the mean of 80±15 at the time of presentation to 50±9.27. When these patients were seen after 8 weeks, the pain reduction on VAS was nil in 21 patients out of 25. In group 2 the mean score fell from 75±15 to 20±10 after 4 weeks and at 8weeks 23 out of 25 patients didn't have any pain. It was observed that the pain reduction and healing were faster in group 2 patients when evaluated after 4 weeks (p=0.0029). but at the end of 8 weeks both group patients were similar in terms of pain reduction and healing of fissure (p=.28).Conclusion: According to study local GTN application is as effective as lateral sphincterotomy with cost effectiveness, simple with tolerable side effect and no continence disturbances.